2016
DOI: 10.3389/fpsyg.2016.00446
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a German Version of the Ethical Leadership at Work Questionnaire by Kalshoven et al. (2011)

Abstract: The present study evaluates the psychometric properties of a German version of the Ethical Leadership at Work questionnaire (ELW-D), and further embeds the construct of ethical leadership within its nomological network. Confirmatory factor analyses (CFAs) based on the total sample of N = 363 employees support the assumed seven-factor structure of the German translation. Within a sub-sample of N = 133, the ELW-D shows positive correlations with related leadership behaviors (transformational leadership, continge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…Specifically, De Hoogh and Den Hartog (2008) and Kalshoven et al (2011, 2013) identified seven behavioral dimensions of ethical leadership: fairness , power sharing , role clarification , ethical guidance , people orientation , concern for sustainability , and integrity . First, ethical leaders are expected to be fair in their decisions, which entails being transparent, taking principled, balanced decisions (Kalshoven et al, 2011; Steinmann et al, 2016), being honest, acting responsibly, and treating employees equally (Kalshoven et al, 2013). Ethical leaders are also expected to share power (Kalshoven et al, 2011, 2013), which refers to allowing employees to participate in decision making, and listening to their ideas and opinions (Brown et al, 2005; De Hoogh and Den Hartog, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, De Hoogh and Den Hartog (2008) and Kalshoven et al (2011, 2013) identified seven behavioral dimensions of ethical leadership: fairness , power sharing , role clarification , ethical guidance , people orientation , concern for sustainability , and integrity . First, ethical leaders are expected to be fair in their decisions, which entails being transparent, taking principled, balanced decisions (Kalshoven et al, 2011; Steinmann et al, 2016), being honest, acting responsibly, and treating employees equally (Kalshoven et al, 2013). Ethical leaders are also expected to share power (Kalshoven et al, 2011, 2013), which refers to allowing employees to participate in decision making, and listening to their ideas and opinions (Brown et al, 2005; De Hoogh and Den Hartog, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Under ethical leadership conditions, employees are more likely to feel less fear, more security (Sharif and Scandura, 2014; Neves et al, 2018), more information about the situation, and a greater sense of control (Morgan and Zeffane, 2003), which is key for them to offer their best response to any change process (Vakola and Nikolaou, 2005). Furthermore, ethical leaders empower people (Kalshoven et al, 2011, 2013), so they are more likely to promote employees’ involvement in the change process (i.e., voice in the change process; Sharif and Scandura, 2014), by reflecting confidence in employees’ abilities, thus increasing their self-efficacy perceptions (Abrell-Vogel and Rowold, 2014; Steinmann et al, 2016). Such enhancement in their self-efficacy perceptions is critical to understanding and responding to the environment in an efficient manner (Bandura, 2001) as well as to be ready for any change (Shah and Shah, 2010; Vakola, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this, the purpose of our study is to empirically examine the effect of both ethical and passive leadership behavior on employee burnout. The non-participation, lack of direction and care, and unresponsiveness of passive leadership contradicts with the consideration and guidance ethical leadership provides (Steinmann et al 2016). Thus, leaders who are seen to act both in ethical and passive ways display inconsistent leader behaviors and research suggests that behavioral inconsistency hampers the clarity and credibility of the leader actions (Johnsen et al 2012).…”
mentioning
confidence: 99%